Discovery of druggable biologics from alternanthera paronychiodes - Ye, Weijian (2013)
Over the years, the chemical profiles of numerous herbs have been characterized, the majority of which are non-peptide compounds. This could be due to the novelty of the idea of peptides being a biologically active compound, and hence are not actively being screened for. Recently, it was found that Viola Yedoensitis (Violaceae), 紫花地丁, a Chinese medicinal herb, contains biologically active cyclotides (Wang, Colgrave et al. 2007). [1st Award]